(untitled) (Journal of Asian Development Studies, 2025)
Social media has made our lives easier in many ways, such as in business, communication, and education; however, its problematic use can be detrimental to mental health. The objective of this study is to examine the effects of problematic social media use on cyberbullying perpetration, mediated by narcissistic traits and moderated by empathy and social support among young adults in Pakistan. The study adopted a cross-sectional correlational design and purposive sampling technique to collect data from 257 individuals aged 18 to 25 (M age = 22.18, SD age = 1.91), including 192 men and 65 women, who had been using social media for at least the past year. Five scales were utilized: the Bergen Social Media Addiction Scale, the perpetration subscale of the Cyber-bullying Perpetration and Victimization Questionnaire (to measure cyberbullying perpetration only), the Narcissism Short Form Scale (to measure narcissistic traits), the Basic Empathy Scale, and the Social Support Scale (Short Form). The correlational results indicate that problematic social media use has a positive and significant association with narcissistic traits and cyberbullying perpetration. In contrast, its association with social support and empathy is negative but insignificant. According to Hayes Process 4.1 (Model 1), narcissistic traits significantly and positively mediate the association between problematic social media use and cyberbullying perpetration.